Attaining environmental sustainability amidst the interacting forces of natural resource rent and foreign direct investment: Is Norway any different? - Udemba, Edmund Ntom (2024)
This is a study of Norway's sustainable environment development amidst the interactions of natural resources, external investment (FDI) and economic development. Much has been done with respect to the study of Norway's economic performance in relation to the link between the natural resources and FDI with little emphasis on the environmental performance of the resource-based economy. Also, Norway is classified as among the top countries in Europe with a greater percentage of adopting renewable energy, and no study has done a critical review of the impact of natural resources and FDI which are part of drivers of carbon emission that can counter the positive impact of renewable energy towards the Norway's sustainable environment. On this basis, this study adopts a time series data of Norway, 1970 to 2018 to study its environmental performance. Approaches such as structural break analysis, Autoregressive Distributed Lag (ARDL)-bound testing and Granger causality estimations are utilised in this study for in-depth analysis of the subject. Findings from ARDL confirmed a positive association between fuels and carbon emission, other indicators (economic growth and natural resources) are improving the quality of the country's environment. FDI even though shows positive sign remains insignificant in impacting the environmental performance in the short run reverted to a significant negative relationship with carbon emissions. This confirms the pollution halo hypothesis and rejects the pollution haven hypothesis (PHH) for Norway, and this trend can be sustained with the constant implementation of environmental rules in the country. Granger test confirms, a one-way transition from fossil fuels to carbon emission, from carbon emission to growth, and from economic growth to fossil fuels. Also, a two-way transmission is found between fossil fuels and FDI. These findings from Granger causality are consistent with the findings from ARDL, hence, two ways interactions between FDI and fossil fuel energy source consumption from Granger causality and the two variables (fossil fuels and FDI) are seen impacting on Norway's environmental performance. Findings from the estimates suggest that natural resources and FDI are mitigating pollution, hence, Norway's policy is expected to be resources and FDI driven in sustainable environment development.